Game Development With Python: Let’s Build a Simple Games! - Mochammad Gendry Afriansyah; Sandhi Alfianda Ghifari; Muhammad Taqi Wijdan; Rifki Syarif Hidayat; Muhammad Ni’am Syukri; Nurvelly Rosanti; Mirza Sutrisno; Sitti Nurbaya Ambo; Yana Adharani; Popy Meilina (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
The development of technology opens up opportunities for individuals to develop new skills, including in the increasingly popular game industry. To provide a basic understanding of game development, a Webinar and Workshop entitled “Game Development With Python: Let's Build a Simple Game!”. This activity consists of material presentation sessions in the Webinar and hands-on practice in the Workshop. Evaluation through questionnaires showed positive responses to the presenters and the material presented. Of the 37 participants who participated, the Pre-Test and Post-Test results showed an increase in understanding with an average initial score of 67.3% which increased to 89.4%. A total of 67.6% of participants expressed very satisfied, while 32.4% were satisfied. These results show that this activity succeeded in increasing participants' understanding and skills in developing simple games using Python, as well as making a positive contribution to students and the general public.